Strengthening the research agenda of educational integrity in Canada: a review of the research literature and call to action - Sarah Elaine Eaton; Rachael Ileh Edino (International Journal for Educational Integrity, 2018)
Abstract We present findings of a literature review on the topic of educational integrity in the Canadian context. Our search revealed 56 sources, published between 1992 and 2017. A historical overview showed a rise in the number of scholarly publications in recent years, but with an overall limited number of research contributions. We identified three major themes in the literature: (a) empirical research; (b) prevention and professional development; and (c) other (scholarly essay). Our analysis showed little evidence of sustained research programs in Canada over time or national funding to support integrity-related inquiry. We also found that graduate students who completed their theses on topics related to educational integrity often have not published further work in the field later in their careers. We provide five concrete recommendations to elevate and accelerate the research agenda on educational integrity in Canada on a national level. We conclude with a call to action for increased research to better understand the particular characteristics of educational integrity in Canada.